Formação contínua e aprendizagem intergeracional na economia da atenção: evidências de uma ação de curta duração com docentes portugueses (Revista Lusófona de Educação, 2026)
Continuous teacher education and intergenerational learning in the attention economy: evidence from a short training course with Portuguese teachers AbstractThe attention economy poses growing challenges to teaching, affecting students’ focus, self-regulation and engagement. In this context, the teaching profession, marked by substantial generational heterogeneity, experiences these challenges unevenly due to differences in career trajectories and levels of digital literacy. This study examines the potential of continuous teacher education as a space for intergenerational learning, drawing on a Short Training Course delivered online to Portuguese teachers. The training, organised into two three-hour sessions, involved 53 teachers of different educational levels, subject areas and professional backgrounds. A mixed-methods approach was used, combining pre- and post-training questionnaires with observation and thematic analysis. The results show significant progress in critical digital literacy: more than 70% of teachers advanced at least one conceptual level, and over 90% reported increased confidence to address the topic with their students. Qualitative analysis reveals intergenerational exchanges of knowledge throughout the course, combining long-established pedagogical strategies with emerging digital practices, as well as shared concerns regarding digital mediation within families. The findings suggest that training initiatives focused on critical digital literacy may provide a relevant contribution to strengthening pedagogical competences and promoting intergenerational learning opportunities within the teaching profession.Keywords: attention economy; continuous teacher education; digital literacy; intergenerationality; professional development.